Estimation of Aquifer Parameter of Pabna District, Bangladesh (Global Journal of Science Frontier Research, 2013)
The amount of groundwater in any area depends on the characters of the underlying aquifer, its extent and the frequency of discharge. Quantitative hydro-geological studies of aquifer parameters are important pre-requisites for scientific management of groundwater resources. Lithological data can be used as an important source for hydro-geological investigation. In this work, the lithological character encountered in borehole of 303 locations and static water levels of 81 locations have been collected, compiled, processed, analyzed and interpreted for studying the hydro-geological properties of nine upazillas of Pabna district, Bangladesh. Various types of map of hydro-geological properties of subsurface formation like porosity, specific yield, transmissivity, hydraulic diffusivity have been prepared for the proper identification of groundwater occurrence, distribution and potentiality of the area studied. Porosity and specific yield are the two important properties of an aquifer material to identify the storage of the aquifer. The yield determines whether or not the water saturated zone is a source of groundwater and the natural characteristics of the water bearing formations affect the yield. The transmissivity map represents its average water transmitting property which depends mainly on the number and diameter of the pores present and determines the effectiveness of groundwater reservoir. Hydraulic diffusivity determines the time that is need for a given head change to occur in an aquifer as a response to a great change in head at another point. Finally, groundwater potential zones have also been identified for groundwater exploration
Keywords: Hydraulic diffusivity determines effectiveness of groundwater reservoir